Kalahari - Khoury, Jessica, 1990- (Razorbill, an imprint of Penguin Group (USA) LLC, 2015)
"Deep in the Kalahari Desert, a Corpus lab protects a dangerous secret. But what happens when that secret takes on a life of its own? When an educational safari goes wrong, five teens find themselves stranded in the Kalahari Desert without a guide"--Provided by publisher.